Isolation of Cellulose Nanofibers from Oryza sativa Residues via TEMPO Mediated Oxidation. Issue 4 (3rd April 2022) - Madivoli, Edwin S.; Kareru, Patrick G.; Gachanja, Anthony N.; Mugo, Samuel M.; Sujee, David M.; Fromm, Katharina M.
ABSTRACT: Cellulose nanocrystals (CNCs) or cellulose nanofibers (CNFs) with different morphologies, chemical, mechanical and physical properties can be obtained when microcrystalline cellulose is subjected to enzymatic, chemical or mechanical treatment. With the aim of utilizing cellulose nanofibrils (CNFs) from Oryza sativa, we isolated microcrystalline cellulose using the Kraft process, followed by successive fiber fibrillation using mechanical grinding, then (2, 2, 6, 6-Tetramethylpiperidin-1-yl)oxyl (TEMPO) mediated oxidation. Analysis of pulp fibers obtained after each treatment step revealed that fiber properties such as length, crystallinity and crystal size changed when the pulp was subjected to mechanical grinding, ultrasonication and TEMPO mediated oxidation. The degree of crystallinity of the fibers increased while crystal size and fiber length decreased after each treatment. TEMPO mediated oxidation led to a decrease in fiber length and an increase in degree of crystallinity of the fibers as compared to mechanical treatment and ultrasonication. It further introduced carboxyl functional groups (COOH) on the surface of the fibrils, which implies that the nanofibers obtained in this study could be further functionalized. Hence, TEMPO mediated oxidation offers the possibility of further chemical functionalization of cellulose nanofibers isolated from agricultural residues.